Possibilities of Digitalization of the Qualification Thesis Topic Submission Process - KLEMENT, MILAN (Journal of Education, Technology and Computer Science, ISSN 2719-6550, e-ISSN 2719-7417, 2023)
The challenges associated with the process of awarding and processing qualification work can be traced both in the area of efforts to improve the quality of this specific process and in the area of supporting the digitisation of the study agenda in general. Given that the core processes at the university rely on highly skilled professionals, digitising processes is not as straightforward as it would be for more mechanical work. Although universities have a long tradition of organising work, they have not yet paid much attention to digitised processes. For this reason, we developed and piloted a flexible electronic workflow for digitizing a selected process and tested it under real-life conditions, including the implementation of qualitative research. The results show the usefulness and adaptability of the proposed electronic workflow from the perspective of its users.